Impact of ESG Implications on HR Roles - A Case Study of Retail Business in Thailand - Jarusarn, Panjai; Petchsawang, Pawinee (ABAC ODI JOURNAL Vision. Action. Outcome, 2025)
With the implementation of the Stock Exchange of Thailand (SET) disclosure requirements, the Environmental, Social, and Governance (ESG) principles are gaining prominence in Thailand. Human Resource (HR) practitioners are increasingly tasked with supporting sustainability initiatives and engaging diverse stakeholders. This study explores the impact of ESG integration on HR practitioners within a Thai retail company, drawing on Strategic Human Resource Management (SHRM) and Stakeholder Theory. Using a qualitative approach, semi-structured interviews were conducted with HR practitioners. The collected data was analyzed to find common themes. Findings reveal two pathways. First, ESG acts as a catalyst that directly reshapes HR roles into new positions such as ESG Talent Developer and Green HRM Practitioner. Second, ESG acts as a validator of existing HR practices that already support stakeholder value, including Internal and External Stakeholder Advocates. A third insight highlights a boundary condition that ESG’s influence is limited unless HR leaders possess sufficient business acumen to balance profitability and sustainability. These findings contribute to the literature on HR role transformation and ESG integration, emphasizing the relevance of Stakeholder Theory in navigating interconnectedness, value creation, and stakeholder balance.